Ecumenismo e militância religiosa: o protestantismo como objeto de estudo / Ecumenism and religious militancy: Protestantism as an object of study - Watanabe, Tiago Hideo Barbosa (PLURA, Revista de Estudos de Religião / PLURA, Journal for the Study of Religion, 2012)
Os primeiros estudos sobre o protestantismo brasileiro realizados na academia brasileira surgiram com regularidade a partir dos anos 1970. Neste artigo, mostraremos a interação dos três principais locais de produção desses primeiros estudos: o primeiro, situado fora do Brasil, relativo a uma produção de dissertações e teses defendidas em seminários e universidades norte-americanas; o segundo, artigos e livros financiados por organismos ecumênicos nacionais e internacionais; e, por fim, a produção dos departamentos de Ciências Humanas das universidades brasileiras. Mostraremos que a proposta de mudança eclesiástica protestante em favor do ecumenismo perpassou esses três cenários influenciando consideravelmente o nascimento do estudo acadêmico do protestantismo no Brasil. Apresentaremos elementos para um debate a respeito de alguns dos limites e implicações que essa “opção ecumênica” teve para a compreensão do protestantismo brasileiro. Abstract The first studies of Brazilian Protestantism made by the Brazilian academy started appearing regularly in the 1970’s. This article points out the interaction among three main places where those studies were originally produced: the first one, situated outside Brazilian borders, refers to the production of thesis and dissertations in North-American universities and seminaries; the second is related to articles and books funded by national and international ecumenical bodies; the third is the academic production of Human Sciences departments in Brazilian universities. It is demonstrated that the intention of ecclesiastical protestant change in favor of ecumenism was present at those three main scenarios and has influenced the beginning of the academic studies of Protestantism in Brazil. Some elements are also presented to support a debate regarding the limits and implications of this “ecumenical option” to the comprehension of Brazilian Protestantism.